Ազգագրական-ժողովրդական երկու նշխարերգ՝ Այնճարէն եւ 1940ականներու Պէյրութէն ու միքանի այլ յանգաւոր գրութիւններ/երգեր - Տագէսեան, Անդրանիկ (տպ. Atlas)
The paper introduces a number of songs and rhymed writings which were sung and recited among the Lebanese Armenian circles of the 1940s and 1950s. The first is an ethnographic song from Musa Ler/Anjar. It is the song sung during the departure of the bride from her paternal home. Both the lyrics and music of the one published here are a variation of the one published in the ethnographic song book of Musa Ler/Anjar. The second song, which is an unpublished song sung in the Jibeil Birds’ Nest Orphanage and indeed in Anjar, too, during the 1940s and 1950s, is about the bite of the mosquito which causes malaria. The song describes the consequences of the bite of the mosquito and how the victim suffered and had no choice but to seek the advice of the doctor, who prescribed a number of injections, which eventually improved the health of the victim. The music of the song has been retrieved and published alongside the lyrics. One of the three other rhymed writings, named “Dandigin Guzenk” (We Want a Housewife), was published in a book in 1913 in Boston. The last two, however, seem to be heretofore unpublished. The music for these three poems has not been retrieved so far. The paper notes that all five of these songs were frequently sung in the 1940s and the 1950s in Lebanese Armenian circles.
Keywords: Հրապարակումներ; Ժողովրդական երաժշտութիւն; Ազգագրութիւն